Characterization and identification of sediment forming agents in barberry juice. (15th May 2020) - Mousavi, Sayed Mohammad Ebrahim; Mousavi, Mohammad; Kiani, Hossein
Highlights: FTIR, HPLC and LC-MS were used to characterized barberry sediment. Sugar derived organic acids were present in barberry juice and sediment. Sugar derived acids with carboxylic groups caused instability in barberry juice. Nucleation, crystal growth and crystal shape were affected by juice concentration. Abstract: Cloud and sediment formation is a major problem in juices and drinks. Barberry juice, as a functional and healthy product, is faced with the sedimentation problem, as an emerging issue. The present study was carried out to identify the sediment forming agents in barberry juice concentrate. The sediment was characterized by a range of different analytical techniques including FTIR, UV spectrophotometry, HPLC and LC-MS analysis. The findings of this research revealed that sugar derived organic acids, which were present in high amounts in barberry juice, were mainly responsible for sedimentation of barberry juice concentrate during cold storage. It was reported that such sugar derived acids with active carboxylic groups could cause instability in products rich in these compounds. The isolated sediment could re-crystalize at different juice concentrations with different shapes and sizes as affected by nucleation and crystal growth rates.